Genomic Characterization and Virulence Potential of Two Fusarium oxysporum Isolates Cultured from the International Space Station - Camilla Urbaniak (American Society for Microbiology, 2019)
ABSTRACT Two isolates of Fusarium oxysporum, ISS-F3 and ISS-F4, were cultured from the dining table on the International Space Station (ISS). Genomic analyses using EF-1α sequences, presence/absence of effector proteins, k-mer comparisons, and single nucleotide polymorphisms indicate that these two strains are genomically different from 65 known sequenced strains. Functional analysis revealed that ISS-F3/F4 had higher relative abundances of polyketide synthase domains than a non-plant-pathogenic soil isolate, used for biocontrol properties (Fo47), and a clinical isolate (FOSC-3a). Putative secondary metabolite analysis indicates that ISS-F3/F4 may produce yet-unreported polyketides and nonribosomal peptides. While genomic analysis showed that these ISS strains are unlikely to be plant pathogens, a virulence assay using an immunocompromised Caenorhabditis elegans model of fusariosis revealed that they were virulent and may represent opportunistic pathogens in animals, including humans. However, its effects on the health of immunocompromised humans warrant further study. IMPORTANCE This is the first study to isolate and characterize F. oxysporum isolates from a built environment, as well as one that has been exposed to space. The characterization and analysis of these two genomes may have important implications for the medical, agricultural, and food industries as well as for the health of the crew who coinhabit the ISS with these strains.